Evaluation of palliative treatments in unresectable pancreatic cancer. Issue 5 (18th April 2021) - Choi, Colin Chan‐Min; Choi, Julian; Houli, Nezor; Smith, Marty; Usatoff, Val; Lipton, Lara; Chan, Steven
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) presents as unresectable disease in 80% of patients. Limited Australian data exists regarding management and outcome of palliative management for PDAC. This study aims to: (i) identify patients with PDAC being managed with palliative intent; (ii) assess the type of palliative management being used. Methods: A prospectively maintained pancreatic database at Western Health (2015–2017) was used to identify patient demographics; stage and multidisciplinary decision regarding resectability and operative interventions; palliative care; use of chemotherapy, radiotherapy and; management of exocrine and endocrine insufficiency. Data on chemotherapy use, number of hospital admissions, emergency department attendances and intensive care unit admissions 30 days prior to death were recorded. Results: One‐hundred and eleven patients had diagnosis of PDAC, 15% with locally advanced and 45% with metastatic PDAC. Among the locally advanced and metastatic PDAC, 48% received biliary stent insertions, 93% had palliative care referral, 45% received palliative chemotherapy and 10% received radiotherapy. Dietitian referral occurred in 79% and 36% were prescribed with a pancreatic enzyme replacement therapy. Diabetes mellitus was present in 52% of which 31% was new onset. Within 30 days prior to death, 11% patients received palliative chemotherapy, 32% were hospitalized and 11% visited an emergency department more than once. Sixty‐five percent died in hospital. Conclusion: A high proportion of patients diagnosed with locally advanced and metastatic PDAC received palliative care referrals and appropriate level of end‐of‐life care. Further prospective studies are necessary, examining the management and impacts of pancreatic insufficiency in this group. Abstract : This study presents comprehensive data on patients with locally advanced and metastatic pancreatic ductal adenocarcinoma in real‐life practice in local Australian setting. A large proportion of patients received adequate palliative care at the institution with appropriate level of aggressiveness of end‐of‐life care. Further prospective studies are necessary for examining the management and impacts of pancreatic insufficiency in this group.